EFL students’ perceptions of oral presentations: Implications for motivation, language ability and speech anxiety - Gürbüz, Cem; Cabaroğlu, Neşe (Selcuk University, 2021)
In this study, we investigated preparatory class students’ perceptions of oral presentations and their functions in EFL learning and teaching in connection with language ability, speech anxiety, and language learning motivation. Our participants were 29 adult EFL students in two intact classes attending a mandatory English preparatory program at a state university, who performed up to three controlled oral presentations following preliminary instruction. We collected data through pre-and post-student surveys, semi-structured interviews, self-reflection forms, and peer-evaluation forms. The pre-survey results revealed that the participants already held positive perceptions of oral presentations despite perceived difficulties. The post data showed significant changes in a positive direction in four variables, namely unwillingness, experience and perception of oral presentations, and language skills. The findings from the qualitative data also confirmed that the participants had benefited from their supervised oral presentations in terms of overcoming their speaking anxiety and perceived significant improvements in a range of language skills including pronunciation and public speaking. © 2021 Cognizance Research Associates - Published by JLLS.
Keywords: Language ability; Language learning motivation; Oral presentations; Speaking anxiety; Speaking skills